2014
DOI: 10.1016/j.aquatox.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative responses to endocrine disrupting compounds in early life stages of Atlantic salmon, Salmo salar

Abstract: a b s t r a c tAtlantic salmon (Salmo salar) are endangered anadromous fish that may be exposed to feminizing endocrine disrupting compounds (EDCs) during early development, potentially altering physiological capacities, survival and fitness. To assess differential life stage sensitivity to common EDCs, we carried out short-term (4 day) exposures using three doses each of 17 ␣-ethinylestradiol (EE2), 17 ␤-estradiol (E2), and nonylphenol (NP) on four early life stages; embryos, yolk-sac larvae, feeding fry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 76 publications
4
22
3
1
Order By: Relevance
“…Regarding the sex steroid levels, the endocrine system in males and juvenile fish was more affected than that in females. Similar observations concerning differential life stage sensitivity have been reported in other studies (Duffy et al, 2014;Liney et al, 2005). Moreover, antiandrogenic effects may be provoked by inhibition of testosterone synthesis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Regarding the sex steroid levels, the endocrine system in males and juvenile fish was more affected than that in females. Similar observations concerning differential life stage sensitivity have been reported in other studies (Duffy et al, 2014;Liney et al, 2005). Moreover, antiandrogenic effects may be provoked by inhibition of testosterone synthesis.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, in vivo studies have indicated that substituted phenols can alter the expression of the steroid receptors associated with changes in the metabolism of xenobiotics and steroid hormones (Zhang et al, 2008). Therefore, potent estrogenic effects of substituted phenols (e.g., Nonylphenol and Tribromophenol) have been found in vitro (Bonefeld-Jorgensen et al, 2007) and in vivo (Deng et al, 2010;Duffy et al, 2014). However, the impact on the endocrine system is not the same as that of natural hormones because the estrogenic effects of substituted phenols are weak.…”
Section: Introductionmentioning
confidence: 99%
“…Atlantic salmon [37,38] but was not observed in brown trout [11]. One possible explanation for this apparent discrepancy between brown trout and grayling larvae is that hatching was not induced in the study on brown trout [11] but induced by an increase in temperature in the present study on grayling.…”
Section: Such a Reduction In Growth Was Predicted From Recent Analysecontrasting
confidence: 59%
“…Akaike's information criteria (AIC) were used as measures of model fit and model complexity, and likelihood ratio tests (LRT) were used to compare models. All the mixed-effects models were fitted with the lme4 R package[36] and all the statistical analyses were performed in R[37].…”
mentioning
confidence: 99%
“…Marques da Cunha et al [11] found EE2 to reduce embryo survival by only 0.9 percent points, and they found no additive genetic variance for the tolerance to EE2 in seven genetically distinct populations. Duffy et al [23] found no EE2-induced mortality in embryos and larvae of Atlantic salmon. They also studied vitellogenin gene transcription and plasma concentrations and found this precursor egg protein to be significantly affected only in embryos exposed to EE2 concentrations that may be too high to be ecologically relevant.…”
Section: Introductionmentioning
confidence: 97%